Gambaran Indeks Eritrosit Pada Penderita Tuberkulosis Paru di Rumah Sakit Umum Mary Cileungsi Bogor - Kristianingsih, Yuli; Rahayu, Cahyawati; Prakoso, Aryo; Pratiwi, Cindy Dui (Anakes : Jurnal Ilmiah Analis Kesehatan, 2024)
Tuberculosis is a chronic disorder that spreads to several organs. It is caused by bacteria (Mycobacterium tuberculosis), which primarily affects the lungs. Cases remain high in the community, making it a global health issue. Tuberculosis can cause hematological disorders, affecting hematopoietic progenitor cells and plasma components, particularly erythrocytes. The examination of erythrocyte indices in pulmonary tuberculosis patients aims to determine the type of anemia. The purpose of this study is to describe the erythrocyte index values in pulmonary tuberculosis patients at Mary Cileungsi General Hospital, Bogor. This study is quantitative research using secondary data collected from medical records and then processed. The study involved 80 tuberculosis patients. The results showed that 48 patients (60%) had normal MCV, 30 patients (37%) had low MCV, and 2 patients (3%) had high MCV. For MCH, 48 patients (60%) had normal values, 30 patients (37%) had low values, and 2 patients (3%) had high values. Regarding MCHC, 69 patients (86%) had normal values, 8 patients (10%) had low values, and 3 patients (4%) had high values. The study concluded that there was an increase in erythrocyte indices in tuberculosis patients, both male and female, with an increase across all age groups. It is recommended to take medication regularly to reduce the risk of transmission. Additionally, this information can be useful in conducting erythrocyte index examinations to detect and prevent early indications of anemia. Keywords : Anemia, Erythrocyte index values, Pulmonary tuberculosis patients